Stylistic Analysis of Verbal Humors Presented in Stand-Up Comedy Show: The Figurative Language Analysis of Raditya Dika’s Verbal Humors - Putri, Ika Dewita; Irawan, Andi Muhammad (English Language and Literature, 2024)
This research is analyzing the use of figurative language used in stand-up comedy show presented by Raditya Dika. This research uses the theory by Kennedy in 1979 as the main theory, and Theory by Davis (2016) as the supporting theory. The aim of this research is to find out the type of figurative language used in verbal humor presented by Raditya Dika in stand-up comedy show in 2017 and 2019. Also, this research aims to find the differences between the use of figurative language by Raditya Dika in stand-up comedy show in 2017 and 2019.This is a qualitative research. The researcher uses qualitatuve method in order make the reader understand by describing and explaining the findings. The data of this research is stand-up comedy by Raditya Dika in 2017 and 2019. The data is taken from Raditya Dika’s youtube Channel.There are 69 figurative language which are found by researcher in Raditya Dika’s stand-up comedy show in 2017 and 2019. In 2017, there are 33 figurative languages. Those 33 figurative languages are divided into 6 types. They are simile (11), metaphor (11), irony (4), personification (3), hyperbole (3), and meiosis (1). In 2019, there are 36 figurative languages. Those 36 figurative languages are divided into four types. They are simile (6), metaphor (17), Irony (5), and hyperbole (8). In 2017, figurative language types that most used by Raditya Dika is simile (11) and metaphor (11). Then, the less used figurative language is meiosis (1). While, in 2019, the most used figurative language type is metaphor (17) and the less used is irony (5). There is no personification and meiosis which are found in Raditya Dika’s stand-up comedy show in 2019.